A systematic review of the effectiveness of advanced practice nurses in long‐term care. (25th March 2013) - Donald, Faith; Martin‐Misener, Ruth; Carter, Nancy; Donald, Erin E.; Kaasalainen, Sharon; Wickson‐Griffiths, Abigail; Lloyd, Monique; Akhtar‐Danesh, Noori; DiCenso, Alba
Abstract Aim To report quantitative evidence of the effectiveness of advanced practice nursing roles, clinical nurse specialists and nurse practitioners, in meeting the healthcare needs of older adults living in long‐term care residential settings. Background Although studies have examined the effectiveness of advanced practice nurses in this setting, a systematic review of this evidence has not been conducted. Design Quantitative systematic review. Data sources Twelve electronic databases were searched (1966–2010); leaders in the field were contacted; and personal files, reference lists, pertinent journals, and websites were searched for prospective studies with a comparison group. Review methods Studies that met inclusion criteria were reviewed for quality, using a modified version of the Cochrane Effective Practice and Organisation of Care Review Group risk of bias assessment criteria. Results Four prospective studies conducted in the USA and reported in 15 papers were included. Long‐term care settings with advanced practice nurses had lower rates of depression, urinary incontinence, pressure ulcers, restraint use, and aggressive behaviours; more residents who experienced improvements in meeting personal goals; and family members who expressed more satisfaction with medical services. Conclusion Advanced practice nurses are associated with improvements in several measures of health status and behaviours of older adults in long‐term care settings and in family satisfaction. Further exploration is needed to determine the effect of advanced practice nurses on health services use; resident satisfaction with care and quality of life; and the skills, quality of care, and job satisfaction of healthcare staff.